Blade of the Immortal. omnibus VII - Samura, Hiroaki (Dark Horse Manga, a division of Dark Horse Comics, Inc., 2018)
In the tunnels beneath Edo Castle, Rin and Doa search for their missing loved ones and face a seemingly endless run of strange foes. Dishonored military leader Kagimura must destroy Anotsu and the hated Itto-ryū school, so he forms the new Rokki-dan gang of odd criminal misfits to help him track Anotsu down.